A new rice variety with high yield released in Madagascar for low land ecology (FOFIFA 187) - CGIAR Research Program on Rice (2019)
High yielding variety released by the National Varietal Release Committee (SOC). We have produced breeder and foundation seeds. The foundation seed is delivered to the seed producers associations, who are now cultivating certified seeds.